The performance identification of gripper by isocline analysis. (16th March 2020) - Chuang, Yun-Ju; Tsung, Tsing-Tshih; Chang, Ho; Sun, Yin-Tung
In this work, a way to identify the performance and adjustment of the gripper was proposed by isocline analysis. This isocline analysis method is processed in three steps. Initially, the performance of the original gripper was tested, followed by adjusting the size factors of the gripper, and finally the boundary curve of the catch range was translated inside. Through these three steps, three results were obtained. First, the original performance of the gripper by step 1 was understood, then the difference between the adjusted gripper and the original gripper by step 2 was noted, and finally, the best position or boundary for this gripper by step 3 was identified. This is a feasible performance test, and it has three advantages. Most important of all, the working range of the gripper is understood. Moreover, the most appropriate working position of the gripper is identified. The results showed that the obtained gripper has the potential to improve performance.